Analisis Pengaruh Kebijakan Deviden Terhadap Nilai Perusahaan - waldelmi, idel (Jurnal Daya Saing, 2015)
Abstract: This study aims to determine Dividend Policy Influence Analysis, Profitability and Institutional Ownership Structure on Capital Structure and Firm Value in companies listed on the Indonesia Stock Exchange. The sample consisted of 38 companies listed on the stock exchanges of Indonesia from 2010 - 2012. The sampling method used is purposive sampling. Data were analyzed using analysis method fath. The results showed Simultaneously ownership, dividend policy variable dividend policy has contributed to the company's value. Positive t value indicates that the variable dividend policy has a direct correlation with the value of the company. Keywords: dividend policy and corporate value.